Fixation using Alternative Implants for the Treatment of Hip Fractures (FAITH-2): The Exploratory Health-Related Quality of Life and Patient-Reported Functional Outcomes of a Multi-Centre 2 × 2 Factorial Randomized Controlled Pilot Trial in Young Femoral Neck Fracture Patients. Issue 10 (October 2021) - Slobogean, Gerard P.; Sprague, Sheila; Bzovsky, Sofia; Scott, Taryn; Thabane, Lehana; Heels-Ansdell, Diane; O'Toole, Robert V.; Howe, Andrea; Gaski, Greg E.; Hill, Lauren C.; Brown, Krista M.; Viskontas, Darius; et al.
Highlights: Clinically significant functional benefits to cancellous screws were observed at 6- and 9-months, but this observation is exploratory and should be viewed cautiously. Supplementation with vitamin D3 4, 000 IU daily did not improve outcomes; however, serum 25(OH)D was not measured to confirm increases in circulating vitamin D levels. The residual functional outcome deficits at 12-months post-fracture exceed the minimum clinically important difference of 5 points for the SF-12. Abstract: Purpose: Femoral neck fractures in young patients are typically managed with internal fixation using either cancellous screws or a sliding hip screw (SHS). Although fixation preserves the hip joint, patients are still at risk of complications and poor clinical outcomes which lead to diminished function and health related quality of life (HRQL). The Fixation using Alternative Implants for the Treatment of Hip Fractures (FAITH-2) pilot randomized controlled factorial trial evaluated the effect of surgical fixation (cancellous screws vs. SHS) and vitamin D supplementation vs. placebo on patient-reported function and HRQL. Methods: Patients between the ages of 18-60 years with a femoral neck fracture requiring surgical fixation were eligible. Eligible patients were randomized to receive either a sliding hip screw or cancellous screws for fracture fixation AND vitamin D3 4, 000 IU or placebo daily for 6 months. Patient-reported function (Hip Outcome Score) and HRQL (Short Form-12) were assessed at standardized time points in the 12 months following their fixation surgery. Patient-reported function and HRQL were summarized using means, SD, and 95% confidence intervals (CIs), or percentages and counts. Longitudinal data analysis with mixed models was used to explore the effect of treatment group and time on the patient-reported function and HRQL. Results: 86 of the 91 patients randomized into the FAITH-2 pilot study were deemed eligible. There were no significant differences in patient-reported function or HRQL between the treatment groups at 12 months post-fracture. At the 6- and 9-month assessments, a potential benefit in hip function was seen in the cancellous screw group. In all treatment groups, participants reported lower function and HRQL at 12 months post-fracture as compared to their pre-injury assessment. Conclusions: Few differences were found in function and HRQL among the treatment groups in the FAITH-2 pilot study. Despite modern implants and vitamin D supplementation, neither function nor HRQL returns to baseline in this population. Additional efforts to improve the outcomes of these challenging injuries are still needed. Level of Evidence: Therapeutic Level II